STRATEGI MARKETING COMMUNICATION INDUSTRI MEDIA CETAK DALAM MENGHADAPI PERSAINGAN (Studi Kasus : Harian Kompas) - Siti Sarah (2020)
At present the more sophisticated the development of technology and information, making print media companies increasingly lost their existence. Seen from the demand for newspapers decreased. Harian Kompas is one of the companies engaged in the print media industry that is currently still sharing information with the public, and can compete with other print media. Kompas Daily certainly has its own marketing communication strategy that keeps its readers in the hearts of readers. The purpose of this study is to analyze marketing communication strategies in the face of competition in the print media industry at Kompas Daily. The method used by research is a qualitative case study. Data collection techniques conducted by researchers are interviews, observation, and documentation. The data analysis technique used is the model of data analysis from Miles and Faisal which consists of data reduction, data presentation, conclusion and verification then the final conclusion. The results of the study found about the marketing communication mix in the Kompas Daily newspaper applying several elements, promoting advertising (advertising), direct marketing (direct marketing), sales promotion (sales promotion), personal selling (personal selling), interactive marketing (interactive marketing, relationships community (public relations) and sponsorship. Keywords: Marketing Communication, Print Media Industry, Competition